Insecticidal Effect and Residual Action of Fenitrothion and Esfenvalerate on Sitophilus oryzae and S. zeamais (Coleoptera: Curculionidae) in Stored Maize and Wheat. (27th August 2012) - Vásquez-Castro, J. A.; de Baptista, G. C.; Gadanha, C. D.; Trevizan, L. R. P.
Abstract : Among the pests that attack stored maize and wheat grain, Sitophilus oryzae (L.) and S. zeamais Motsch (Coleoptera: Curculionidae) are the most destructive. This paper is aimed at the study of the insecticidal effect and the residual action of organophosphate fenitrothion, pyrethroid esfenvalerate, and the mixture of both on S. oryzae and S. zeamais in stored maize and wheat. Grains were treated in order to obtain theoretical concentrations of 10 and/or 0.5 mg·kg −1 fenitrothion and esfenvalerate, respectively. The effectiveness experiments were installed as of 15, and 30 days, and subsequently at monthly intervals as of 12 months after grain treatment, or until mortality ceased in the plots. After mortality evaluation happened all individuals were eliminated, either dead or alive, and grains were kept for 60 days to assess the number of emerged progeny. The comparison of mortality curves of the pest species within each combination of grain type and insecticide showed significant differences. In general, the mortality of S. oryzae decreased faster than that of S. zeamais considering the grain type-insecticide combination. Esfenvalerate was ineffective in all combinations. Higher mortality of both species was observed on wheat grains treated with fenitrothion and fenitrothion + esfenvalerate mixture. Best results as to progeny control were obtained with fenitrothion and fenitrothion + esfenvalerate mixture. The factors that influenced the pest control are discussed in the present work.